2013
DOI: 10.1371/journal.pone.0058242
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glomerular Filtration Rate Estimation by an Artificial Neural Network

Abstract: BackgroundAccurate evaluation of glomerular filtration rates (GFRs) is of critical importance in clinical practice. A previous study showed that models based on artificial neural networks (ANNs) could achieve a better performance than traditional equations. However, large-sample cross-sectional surveys have not resolved questions about ANN performance.MethodsA total of 1,180 patients that had chronic kidney disease (CKD) were enrolled in the development data set, the internal validation data set and the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…GFR was measured by the 99m Tc-DTPA renal dynamic imaging method, 67 as described previously8 According to the method developed by Ma et al,9 we determined the minimum sample size to be 36 (95% confidence interval and 80% power), using Open Epi Version 2 (http://www.openepi.com)10 to compare means (in order to ensure that our measured GFR [mGFR] values were calibrated equally to the dual plasma sample 99m Tc-DTPA-GFR). Calculation was based on the findings in a previous Chinese study11 We randomly selected 36 cases (GFR measured by the DTPA renal dynamic imaging method, range 15.6–106.3 mL/minute/1.73 m 2 ) and performed the dual plasma samples method 99m Tc-DTPA clearance simultaneously with the renal dynamic imaging.…”
Section: Methodsmentioning
confidence: 99%
“…GFR was measured by the 99m Tc-DTPA renal dynamic imaging method, 67 as described previously8 According to the method developed by Ma et al,9 we determined the minimum sample size to be 36 (95% confidence interval and 80% power), using Open Epi Version 2 (http://www.openepi.com)10 to compare means (in order to ensure that our measured GFR [mGFR] values were calibrated equally to the dual plasma sample 99m Tc-DTPA-GFR). Calculation was based on the findings in a previous Chinese study11 We randomly selected 36 cases (GFR measured by the DTPA renal dynamic imaging method, range 15.6–106.3 mL/minute/1.73 m 2 ) and performed the dual plasma samples method 99m Tc-DTPA clearance simultaneously with the renal dynamic imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies reported that ANN and other data mining methods supported medical decisions regarding VUR and some nephrological problems (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…A series of machine learning methods contribute to a speci c improvement for eGFR Eq. (13)(14)(15). However, no prediction equation can comprehensively exceed the CKD-EPI equation.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of standard GFR (sGFR) or measured GFR (mGFR) was radionuclide renal dynamic imaging or 99mTc-DTPA, which was described in detail before (13)(14)(15)22). Serum creatinine (SC) measurement was on Hitachi 7180 auto-analyzer (Hitachi, Tokyo, Japan) using reagents from Roche Diagnostics (Mannheim, Germany).…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation